Laminate and industrial belt

A laminate structure with a specific ethylene-based copolymer composition and fiber material addresses the need for improved productivity and heat aging resistance in industrial belts, achieving high crosslinking rates and extended lifespan.

JP2025044609APending Publication Date: 2025-04-02MITSUI CHEMICALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023152291
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

There is a demand for improved productivity and heat aging resistance in the carcass layer of industrial belts, such as conveyor belts, to enhance their lifespan and performance.

Method used

A laminate structure is developed using an ethylene-based copolymer composition containing specific ratios of ethylene, α-olefin, and non-conjugated polyene units, along with a fiber material, which includes a crosslinking agent to achieve high crosslinking rates and excellent heat aging resistance.

Benefits of technology

The laminate exhibits enhanced productivity and superior heat aging resistance, making it suitable for industrial belts like conveyor belts with improved performance and extended product life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044609000001
    Figure 2025044609000001
  • Figure 2025044609000002
    Figure 2025044609000002
  • Figure 2025044609000003
    Figure 2025044609000003
Patent Text Reader

Abstract

To obtain a laminate including a layer comprising an ethylenic copolymer composition which has a high crosslinking rate and excellent productivity and gives a crosslinked molding excellent in thermal aging resistance.SOLUTION: The laminate includes a layer [I] comprising an ethylenic copolymer composition containing an ethylene / α-olefin / nonconjugated polyene copolymer (A) and a layer [II] containing a fiber material. The layer [I] and the layer [II] are in contact with each other. The copolymer (A) has a structural unit derived from ethylene [A1], a structural unit derived from a C4-20 α-olefin [A2], and a structural unit derived from a nonconjugated polyene [A3] containing two or more partial structures selected from the group consisting of the following general formulae (I) and (II) in total in one molecule and satisfies specific requirements. The structural unit derived from the [A2] contains a structural unit derived from 1-butene, and the structural unit derived from the [A3] contains a structural unit derived from 5-vinyl-2-norbornene.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to laminates and industrial belts. [Background technology]

[0002] Ethylene-α-olefin-non-conjugated polyene copolymers such as ethylene-propylene-diene copolymer (EPDM) have no unsaturated bonds in the main chain of their molecular structure, and therefore have superior heat aging resistance, weather resistance, and ozone resistance compared to general-purpose conjugated diene rubbers. They are widely used in automotive parts, industrial rubber products, electrical insulation materials, building and civil engineering materials, rubberized fabrics, and other applications.

[0003] For example, in industrial belt applications such as conveyor belts, ethylene-α-olefin-non-conjugated polyene copolymers are usually used in the carcass layer of the belt, which requires high elasticity and abrasion resistance.

[0004] In order to satisfy these characteristics, ethylene-based copolymer compositions that have excellent adhesion to layers containing fibrous materials and can maintain the mechanical properties of the resulting laminate have been proposed, including ethylene-α-olefin-non-conjugated polyene copolymers that satisfy specific requirements and ethylene-based copolymer compositions that contain specific additives (e.g., Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-161258 Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been an increasing demand for improved productivity and life span of industrial products. Accordingly, there is also a demand for improved productivity and improved heat aging resistance, for example by further shortening the vulcanization time, in the carcass layer of industrial belts such as transport belts (conveyor belts).

[0007] An object of the present invention is to obtain a laminate including a layer made of an ethylene copolymer composition which has a high crosslinking rate, is excellent in productivity, and gives a crosslinked molded article having excellent heat aging resistance. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by the following configuration, thereby achieving the present invention. A configuration example of the present invention is as follows.

[0009] [1] The present invention relates to a coating composition for a coating film comprising an ethylene-based copolymer composition (A) and a layer (II) containing a fiber material, the layer (I) and the layer (II) being made of an ethylene-based copolymer composition containing an ethylene-α-olefin-non-conjugated polyene copolymer (A). A laminate characterized in that The copolymer (A) has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, A laminate, wherein the structural units derived from the non-conjugated polyene [A3] include structural units derived from 5-vinyl-2-norbornene:

[0010] [ka]

[0011] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of the structural units derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii)

[0012] [2] The laminate according to [1], wherein the copolymer (A) satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (wt%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Requirement (6): Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * (ω=0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * (ω=100) (Pa sec) P〔η * (ω=0.1) / η * (ω=100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv) Requirement (7): Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * (ω=0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * (ω=10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v); Log{η * (ω=0.01)} / Log{η * (ω=10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene [A3]}+1.42 … Formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is -65°C or lower.

[0013] [3] The laminate according to [1] or [2], wherein the copolymer (A) has a Mooney viscosity ML(1+4)100°C of 5 to 150.

[0014] [4] The laminate according to any one of [1] to [3], wherein the ethylene-based copolymer composition contains an organic peroxide as a crosslinking agent (B).

[0015] [5] The laminate according to any one of [1] to [4], wherein the ethylene-based copolymer composition contains 0.1 to 20 parts by mass of a processing aid (C) based on 100 parts by mass of the copolymer (A).

[0016] [6] The laminate according to any one of [1] to [5], wherein the ethylene-based copolymer composition is crosslinked.

[0017] [7] The laminate according to any one of [1] to [6], wherein the fiber material of the layer [II] contains a fiber treated with resorcinol-formaldehyde-latex.

[0018] [8] The laminate according to any one of [1] to [7], wherein the fiber material of the layer [II] is canvas.

[0019] [9] An industrial belt having the laminate according to any one of [1] to [8]. Effect of the Invention

[0020] The laminate of the present invention has excellent productivity because the crosslinking rate of the composition contained in the laminate is high, and the crosslinked molded article obtained from the composition also has excellent heat aging resistance, so that the laminate of the present invention is suitable for industrial belts such as transport belts (conveyor belts). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] [Laminate] The laminate of the present invention (hereinafter referred to as "the laminate") has a layer [I] made of an ethylene-based copolymer composition containing an ethylene-α-olefin-non-conjugated polyene copolymer (A) (hereinafter also referred to as "copolymer (A)"), and a layer [II] containing a fibrous material, and is characterized in that layer [I] and layer [II] are in contact with each other.

[0022] Layer I The layer [I] made of an ethylene-based copolymer composition constituting the present laminate is a layer obtained by crosslinking an ethylene-based copolymer composition containing copolymer (A).

[0023] <Ethylene-α-olefin-non-conjugated polyene copolymer (A)> The copolymer (A) has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4). The structural units derived from the α-olefin [A2] having 4 to 20 carbon atoms include a structural unit derived from 1-butene, and the structural units derived from the non-conjugated polyene [A3] include a structural unit derived from 5-vinyl-2-norbornene.

[0024] [ka]

[0025] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. Requirement (2): The content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]. Requirement (3): The B value represented by the following formula (i) is 1.20 or more. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii)

[0026] Examples of the α-olefins [A2] having 4 to 20 carbon atoms include 1-butene, 1-nonene, 1-decene, 1-nonadecene, 1-eicosene, and the like, which have a linear structure without a side chain; and 4-methyl-1-pentene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and the like, which have a side chain. The structural units of the copolymer (A) derived from the α-olefin [A2] having 4 to 20 carbon atoms include structural units derived from 1-butene, and therefore at least 1-butene is used as the α-olefin [A2].

[0027] As the α-olefin [A2], 1-butene may be used alone or in combination of two or more kinds including 1-butene. When the α-olefin [A2] is used in combination with 1-butene, among these, α-olefins having 4 to 10 carbon atoms are preferred, and 1-hexene, 1-octene, etc. are more preferred.

[0028] Ethylene-propylene-non-conjugated polyene copolymers, in which the α-olefin is propylene, have insufficient rubber elasticity at low temperatures, so their applications may be limited. On the other hand, copolymer (A) has structural units derived from α-olefins [A2] with 4 to 20 carbon atoms, so it has excellent rubber elasticity at low temperatures.

[0029] Examples of the non-conjugated polyene [A3] containing two or more partial structures selected from the group consisting of the general formulae (I) and (II) in one molecule include 5-vinyl-2-norbornene (VNB), norbornadiene, 1,4-hexadiene, and dicyclopentadiene. Since the structural units derived from the non-conjugated polyene [A3] of the copolymer (A) include structural units derived from 5-vinyl-2-norbornene (VNB), at least VNB is used as the non-conjugated polyene [A3].

[0030] As for these non-conjugated polyenes [A3], VNB may be used alone or in combination of two or more kinds including VNB. VNB is highly available, crosslinks well with organic peroxides, and tends to improve the heat resistance of the copolymer composition. As long as the non-conjugated polyene [A3] contains VNB, VNB may be used alone or in combination of two or more kinds including VNB, but it is preferable to use VNB alone.

[0031] The copolymer (A) may contain, in addition to structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], and the non-conjugated polyene [A3], a structural unit derived from a non-conjugated polyene [A4] containing only one partial structure selected from the group consisting of the general formulae (I) and (II) in one molecule.

[0032] Examples of such non-conjugated polyenes [A4] include 5-ethylidene-2-norbornene (ENB), 5-methylene-2-norbornene, 5-(2-propenyl)-2-norbornene, 5-(3-butenyl)-2-norbornene, 5-(1-methyl-2-propenyl)-2-norbornene, 5-(4-pentenyl)-2-norbornene, 5-(1-methyl-3-butenyl)-2-norbornene, 5-(5-hexenyl)-2-norbornene, 5-(1-methyl-4-pentenyl)-2-norbornene, 5-(2,3-dimethyl-3-butenyl)-2-norbornene, 5-(2-ethyl-3-butenyl)-2-norbornene, 5-(6-heptenyl)-2-norbornene, 5-(3-methyl-5-hexenyl)-2-norbornene, 5-(3,4-dimethyl-4-pentenyl)-2-norbornene, 5-(3-ethyl-4-pentenyl)-2-norbornene, 5-(7-octenyl)-2-norbornene, 5-(2-methyl-6-heptenyl)-2-norbornene, 5-(1,2-dimethyl-5-hexenyl)-2-norbornene, 5-(5-ethyl-5-hexenyl)-2-norbornene, 5-(1,2,3-trimethyl-4-pentenyl)-2-norbornene, and the like.

[0033] Among these, ENB is preferred because it is easily available, the crosslinking rate during crosslinking with an organic peroxide is easily controlled, and good mechanical properties are easily obtained. The non-conjugated polyene [A4] can be used alone or in combination of two or more kinds.

[0034] Each of the copolymers (A) may contain at least one biomass-derived monomer (ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], a non-conjugated polyene [A3], and a non-conjugated polyene [A4]).

[0035] The copolymer (A) has a Mooney viscosity at 100°C, ML(1+4)100°C, in the range of preferably 5-150, more preferably 10-100, further preferably 15-50, and particularly preferably 20-40. When the Mooney viscosity ML(1+4)100°C is within the above range, the copolymer obtained has excellent roll processability and flowability, good post-treatment (ribbon handling properties) and excellent rubber properties.

[0036] Requirement (1) The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. The copolymer (A) having a molar ratio in the above range has an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature.

[0037] The lower limit of the molar ratio [A1] / [A2] is preferably 45 / 55, more preferably 50 / 50, even more preferably 55 / 45, and particularly preferably 60 / 40. The upper limit of the molar ratio [A1] / [A2] is preferably 80 / 20, more preferably 75 / 25, and even more preferably 70 / 30.

[0038] Requirement (2) The content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % based on the total of the structural unit derived from ethylene [A1], the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms, and the structural unit derived from the non-conjugated polyene [A3] being 100 mol %. The copolymer (A) having this content in the above range has sufficient crosslinkability and flexibility. In this specification, the content of each structural unit in the resin can be measured by NMR spectrum or the like.

[0039] The lower limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 0.2 mol%, more preferably 0.3 mol%. The upper limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 4.0 mol%, more preferably 3.0 mol%, even more preferably 2.0 mol%, particularly preferably 0.7 mol%. When the content of the structural unit derived from the non-conjugated polyene [A3] is within the above range, a copolymer (A) having sufficient crosslinkability, flexibility, and low-temperature properties can be obtained.

[0040] Requirement (3) The B value represented by the following formula (i) is 1.20 or more, preferably 1.20 to 1.80, more preferably 1.22 to 1.60, further preferably 1.24 to 1.50, and particularly preferably in the range of 1.30 to 1.45. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.]

[0041] An ethylene copolymer having a B value below the above range has a large compression set at low temperatures, and it may not be possible to obtain an ethylene copolymer having an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature. The B value is an index showing the randomness of the copolymerization monomer sequence distribution in the copolymer (A), and [E], [X], [Y], and [EX] in the formula (i) are 13 The amount of carbon ions can be determined by measuring the C-NMR spectrum, based on the reports of JC Randal [Macromolecules, 15, 353 (1982)] and J. Ray [Macromolecules, 10, 773 (1977)].

[0042] Requirement (4) The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii). BrNo≧0.5 …Formula (ii) Here, the number of branch points per molecular chain, BrNo, can be determined by a structural analysis method using 3D-GPC. In this specification, specifically, it was determined as described in the examples described later.

[0043] The copolymer (A) more preferably satisfies the following formula (ii-1). BrNo≧0.8 …Formula (ii-1) It is preferable that the number of branching points per molecular chain satisfies the above formula (ii) or (ii-1), because when a crosslinked molded article is produced, the crosslinking rate is excellent and the molded article after crosslinking exhibits excellent mechanical properties.

[0044] Moreover, the copolymer (A) more preferably satisfies the following formula (ii-2). 3.0≧BrNo…Formula (ii-2) It is preferable that the number of branching points per molecular chain satisfies the above formula (ii-2), since the compression set at low temperatures is small and the balance between rubber elasticity at low temperatures and tensile strength at room temperature is excellent.

[0045] The copolymer (A) preferably satisfies any one or more of the following requirements (5) to (8): The copolymer (A) more preferably satisfies any two or more of the requirements (5) to (8), further preferably satisfies any three or more of the requirements (5) to (8), and most preferably satisfies all of the requirements (5) to (8).

[0046] Requirement (5) The weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (wt%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii): 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Here, the weight average molecular weight (Mw) of the copolymer (A) can be determined as a polystyrene-equivalent value measured by gel permeation chromatography (GPC). In this specification, specifically, it is determined by using 3D-GPC as described in the examples described later.

[0047] The copolymer (A) more preferably satisfies the following formula (iii-1). 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦60 ...Formula (iii-1) The copolymer (A) more preferably satisfies the following formula (iii-2). 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦35 ...Formula (iii-2) When the "Mw × weight fraction of [A3] / 100 / molecular weight of [A3]" satisfies the formula (iii), (iii-1), or (iii-2), the content of the structural unit derived from the non-conjugated polyene [A3] such as VNB is appropriate, and the degree of crosslinking is appropriate. By using this, the crosslinking speed is excellent, and the molded body after crosslinking has a well-balanced excellent mechanical properties and heat aging resistance.

[0048] Requirement (6) Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * (ω=0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * (ω=100) (Pa sec) P〔η* (ω=0.1) / η * (ω=100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv)

[0049] Here, the complex viscosity η at frequency ω=0.1rad / s * (ω=0.1) and the complex viscosity η at frequency ω=100rad / s * (ω=100) Ratio of P〔η * (ω=0.1) / η * (ω=100) ] represents the frequency dependence of viscosity, and corresponds to the left side of the formula (iv) P / ([η] 2.9 ) tends to show high values ​​when there are a lot of long chain branches, although it is affected by factors such as short chain branches and molecular weight.

[0050] Generally, in an ethylene-α-olefin-non-conjugated polyene copolymer, the more structural units derived from non-conjugated polyenes the copolymer contains, the more long chain branches it tends to contain. However, it is considered that copolymer (A) can satisfy the above formula (iv) because it has fewer long chain branches than conventionally known ethylene-α-olefin-non-conjugated polyene copolymers. The copolymer (A) more preferably satisfies the following formula (iv-1). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 5.7 … Formula (iv-1)

[0051] In the present invention, the P value is determined by performing measurements using a viscoelasticity measuring device Ares (manufactured by Rheometric Scientific) at 190° C., a strain of 1.0%, and various frequencies, and is calculated as the ratio (η * The ratio of

[0052] The intrinsic viscosity [η] of the copolymer (A) in requirement (6) means a value measured in decalin at 135°C. The intrinsic viscosity [η] of the copolymer (A) is preferably 2.5 dl / g or less, more preferably 2.0 dl / g or less, further preferably 1.85 dl / g or less, particularly preferably 1.75 dl / g or less.

[0053] Requirement (7) Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * (ω=0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * (ω=10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v). Log{η * (ω=0.01)} / Log{η * (ω=10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene [A3]}+1.42 … Formula (v)

[0054] Here, the complex viscosity η * (ω=0.01) and the complex viscosity η * (ω=10) is the complex viscosity η in requirement (6) * (ω=0.1) and the complex viscosity η * (ω=100) The same procedure is used to calculate the value of the frequency of the measurement. The apparent iodine value derived from the non-conjugated polyene [A3] can be calculated by the following formula: Apparent iodine value derived from [A3] = weight fraction of [A3] × 253.81 / molecular weight of [A3]

[0055] In the formula (v), the left side represents the shear rate dependency which is an index of the amount of long chain branches, and the right side represents an index of the content of the non-conjugated polyene [A3] that is not consumed as long chain branches during polymerization. When the requirement (7) and the formula (v) are satisfied, the degree of long chain branches is not too high, which is preferable. On the other hand, when the formula (v) is not satisfied, it indicates that a large proportion of the copolymerized non-conjugated polyene [A3] is consumed in the formation of long chain branches.

[0056] Requirement (8) The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −65° C. or lower, preferably −67° C. or lower, and more preferably −70° C. or lower. When Tg is within the above range, the obtained molded article has excellent low-temperature properties. Specifically, Tg can be determined by the method described in the Examples below.

[0057] <<Production method of copolymer (A)>> The copolymer (A) can be obtained by various known production methods, for example, a conventionally known production method using a metallocene catalyst that uses a metallocene compound as one component of the catalyst. For example, the examples described in International Publication No. 2015 / 122415, particularly paragraphs

[0249] to

[0320] of the publication, can be adopted as the metallocene catalyst and the production method using the catalyst. Specifically, as described in the examples described later, in the presence of a metallocene catalyst, at least ethylene [A1], an α-olefin [A2] having 4 to 20 carbon atoms, and a non-conjugated polyene [A3] are copolymerized to obtain the copolymer.

[0058] <Other ingredients> The ethylene-based copolymer composition may contain a polymer other than the copolymer (A). Examples of other polymers that require crosslinking include crosslinkable rubbers such as natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, acrylic rubber, silicone rubber, fluororubber, and urethane rubber. Other polymers that do not require crosslinking include, for example, elastomers such as styrene-butadiene block copolymers (SBS), styrene-based thermoplastic elastomers (TPS) such as polystyrene-poly(ethylene-butylene)-polystyrene (SEBS) and polystyrene-poly(ethylene-propylene)-polystyrene (SEPS), olefin-based thermoplastic elastomers (TPO), vinyl chloride-based elastomers (TPVC), ester-based thermoplastic elastomers (TPC), amide-based thermoplastic elastomers (TPA), urethane-based thermoplastic elastomers (TPU), and other thermoplastic elastomers (TPZ).

[0059] The other polymers may be used alone or in combination of two or more. When the other polymer is used, the blending amount in the ethylene copolymer composition is usually 100 parts by mass or less, and preferably 80 parts by mass or less, based on 100 parts by mass of the copolymer (A).

[0060] The ethylene copolymer composition may contain other components according to the desired purpose within the range that does not impair the effects of the present invention. Examples of other components include additives such as crosslinking agents, crosslinking aids, vulcanization accelerators, vulcanization aids, surfactants, fillers, softeners, antioxidants, processing aids, activators, heat stabilizers, weather stabilizers, antistatic agents, colorants, lubricants, thickeners, adhesives, and adhesive aids. Each additive may be used alone or in combination of two or more.

[0061] Crosslinking agent From the viewpoint of improving the crosslinking rate, the ethylene-based copolymer composition preferably contains a crosslinking agent (hereinafter also referred to as "crosslinking agent (B)"). Examples of the crosslinking agent (B) include crosslinking agents generally used when crosslinking rubber, such as organic peroxides, phenolic resins, sulfur-based compounds, hydrosilicone-based compounds, amino resins, quinones or their derivatives, amine-based compounds, azo-based compounds, epoxy-based compounds, isocyanate-based compounds, etc. Among these, organic peroxides and sulfur-based compounds (vulcanizing agents) are preferred.

[0062] Specific examples of organic peroxides include dicumyl peroxide (DCP), di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butylperoxybenzoate, tert-butylperoxyisopropyl carbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.

[0063] Of these, dicumyl peroxide (DCP), 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, and the like are preferred, with dicumyl peroxide (DCP) being more preferred.

[0064] When an organic peroxide is used as the crosslinking agent (B), the blending amount in the ethylene-based copolymer composition is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 15 parts by mass, and further preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the copolymer (A). When the blending amount of the organic peroxide is within the above range, the ethylene-based copolymer composition exhibits excellent crosslinking properties without blooming on the surface of the obtained molded article, which is preferable.

[0065] Examples of sulfur-based compounds (vulcanizing agents) include sulfur, sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, tetramethylthiuram disulfide, and selenium dithiocarbamate.

[0066] When a sulfur-based compound is used as the crosslinking agent (B), the blending amount in the ethylene-based copolymer composition is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 7.0 parts by mass, and even more preferably 0.3 to 5.0 parts by mass, based on 100 parts by mass of the copolymer (A). When the blending amount of the sulfur-based compound is within the above range, there is no bloom on the surface of the obtained molded article, and the ethylene-based copolymer composition shows excellent crosslinking properties.

[0067] ·Crosslinking agent When an organic peroxide is used as the crosslinking agent, it is preferable to use a crosslinking assistant in combination. Examples of the crosslinking aid include sulfur; quinone dioxime-based crosslinking aids such as p-quinone dioxime; acrylic crosslinking aids such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate; allyl crosslinking aids such as diallyl phthalate and triallyl isocyanurate; maleimide crosslinking aids; divinylbenzene; zinc oxide (e.g., ZnO#1, zinc oxide type 2 (JIS K 1410) (manufactured by Hakusui Tech Co., Ltd.), activated zinc oxide "META-Z102" (manufactured by Inoue Sekikogyo Co., Ltd.)), and metal oxides such as magnesium oxide.

[0068] When a crosslinking aid is used, the amount of the crosslinking aid in the ethylene copolymer composition is preferably 0.1 to 30 parts by mass, preferably 1.0 to 20 parts by mass, more preferably 2 to 10 parts by mass, and further preferably 3 to 7 parts by mass, relative to 100 parts by mass of the polymer (A).

[0069] ·Vulcanization accelerator When a sulfur-based compound is used as the crosslinking agent (B), it is preferable to use a vulcanization accelerator in combination. Examples of the vulcanization accelerator include N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, N,N'-diisopropyl-2-benzothiazole sulfenamide, 2-mercaptobenzothiazole (e.g., Suncerer M (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), 2-(4-morpholinodithio)benzothiazole (e.g., Noccelaer MDB-P (trade name; manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)), 2-(2,4-dinitrophenyl)mercaptobenzothiazole, 2-(2,6-dinitrophenyl)mercaptobenzothiazole, Thiazole-based vulcanization accelerators such as ethyl-4-morpholinothio)benzothiazole and dibenzothiazyl disulfide (for example, Sancerer DM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); guanidine-based vulcanization accelerators such as diphenyl guanidine, triphenyl guanidine, and diorthotolyl guanidine; aldehyde amine-based vulcanization accelerators such as acetaldehyde-aniline condensation product and butyraldehyde-aniline condensation product; imidazoline-based vulcanization accelerators such as 2-mercaptoimidazoline; tetramethylthiuram monosulfide (for example, Sancerer DM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (e.g., Sancerer TS (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetramethylthiuram disulfide (e.g., Sancerer TT (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetraethylthiuram disulfide (e.g., Sancerer TET (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetrabutylthiuram disulfide (e.g., Sancerer TBT (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), and dipentamethylenethiuram tetrasulfide (e.g., Sancerer TRA (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); zinc dimethyldithiocarbamate, diethyldithio Examples of such vulcanization accelerators include dithioacid salt vulcanization accelerators such as zinc carbamate, zinc dibutyldithiocarbamate (e.g., Sancerar PZ, Sancerar BZ, and Sancerar EZ (trade names; manufactured by Sanshin Chemical Industry Co., Ltd.)) and tellurium diethyldithiocarbamate; thiourea vulcanization accelerators such as ethylenethiourea (e.g., Sancerar BUR (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.), Sancerar 22-C (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), N,N'-diethylthiourea, and N,N'-dibutylthiourea; and xanthate vulcanization accelerators such as zinc dibutylxatogenate.

[0070] When a vulcanization accelerator is used, the blending amount of the vulcanization accelerator in the ethylene copolymer composition is usually 0.1 to 20 parts by mass, preferably 0.2 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the copolymer (A). When the blending amount of the vulcanization accelerator is within the above range, there is no bloom on the surface of the obtained molded article, and the copolymer composition shows excellent crosslinking properties.

[0071] ·Vulcanization aid When a sulfur-based compound is used as the crosslinking agent (B), a vulcanization aid can be used in combination. Examples of the vulcanization aid include zinc oxide (eg, ZnO#1·zinc oxide type 2 (JIS K 1410) (manufactured by Hakusui Tech Co., Ltd.), activated zinc oxide "META-Z102" (manufactured by Inoue Lime Industry Co., Ltd.)), and magnesium oxide.

[0072] When a vulcanization aid is used, the amount of the vulcanization aid in the ethylene copolymer composition is usually 1 to 20 parts by mass, preferably 2 to 10 parts by mass, and more preferably 3 to 7 parts by mass, per 100 parts by mass of the copolymer (A).

[0073] Surfactants The ethylene copolymer composition preferably contains a surfactant from the viewpoint of adhesion and cohesion with the layer [II] described below. Examples of the surfactant include nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants. Preferably, the surfactant is at least one selected from the group consisting of cationic surfactants and anionic surfactants, and more preferably, a cationic surfactant.

[0074] Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene alkyl ether, polyoxyethylene myristyl ether, polyoxyethylene octyldodecyl ether, polyoxyethylene alkylene alkyl ether, polyoxyethylene distyrenated phenyl ether, polyoxyethylene derivatives, polyoxyethylene polyoxypropylene glycol, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan monostearate. sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, glycerol monostearate, glycerol monooleate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan sesquioleate, polyethylene glycol monolaurate, polyethylene glycol monostearate, polyethylene glycol distearate, polyethylene glycol monooleate, polyoxyethylene hydrogenated castor oil, polyoxyethylene alkylamines, and alkyl alkanolamides.

[0075] Examples of cationic surfactants include coconut amine acetate and stearyl amine. Acetate, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, cetyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, dihydrogenated tallow alkyl dimethyl ammonium chloride, alkyl benzyl dimethyl ammonium chloride, bishydroxyethyl alkyl (C8-18) methyl ammonium chloride, bis (polyoxyethylene) alkyl (C8-18) methyl ammonium chloride, bishydroxyethyl oleyl methyl ammonium chloride. Examples of commercially available cationic surfactants include Lipocard (registered trademark) (e.g., Lipocard 2HT flakes) and Liposocard (registered trademark) (both manufactured by Lion Specialty Chemicals Co., Ltd.).

[0076] Examples of anionic surfactants include mixed fatty acid soda soap, semi-hardened beef tallow fatty acid soda soap, sodium stearate soap, semi-hardened beef tallow fatty acid potassium soap, potassium oleate soap, castor oil potassium soap, sodium lauryl sulfate, sodium higher alcohol sulfate, triethanolamine lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium alkylnaphthalenesulfonate, sodium dialkylsulfosuccinate, sodium alkyldiphenyletherdisulfonate, potassium alkylphosphate, sodium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, sodium alkane sulfonate, and the sodium salt of β-naphthalenesulfonic acid formalin condensate.

[0077] Examples of amphoteric surfactants include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl dimethylamine oxide.

[0078] When a surfactant is used, the amount of the surfactant in the ethylene copolymer composition is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the copolymer (A). When the amount of the surfactant is within the above range, for example, the adhesiveness to a layer containing a fiber material is good, and the crosslinked laminate has excellent adhesive strength to a layer containing a fiber material.

[0079] Filler The filler is one type of known rubber reinforcing agent that is compounded in the rubber composition, and is usually an inorganic substance called carbon black or an inorganic reinforcing agent.

[0080] Specific examples of the filler include Asahi #50HG, Asahi #55G, Asahi #60G, Asahi #60UG, Asahi #70 (all manufactured by Asahi Carbon Co., Ltd.), Seast (V, SO, 116, 3, 6, 9, SP, TA, etc.) carbon black (manufactured by Tokai Carbon Co., Ltd.), these carbon blacks which have been surface-treated with a silane coupling agent or the like, silica, activated calcium carbonate, finely divided talc, finely divided silicic acid, light calcium carbonate, heavy calcium carbonate, talc, clay, etc., of which carbon black, light calcium carbonate, heavy calcium carbonate, talc, and clay are preferred.

[0081] When a filler is used, the blending amount of the filler in the ethylene copolymer composition is preferably 10 to 200 parts by mass, more preferably 20 to 100 parts by mass, further preferably 30 to 80 parts by mass, and particularly preferably 40 to 60 parts by mass, based on 100 parts by mass of the copolymer (A). When the blending amount of the filler is within the above range, a molded product having excellent kneading processability and excellent mechanical properties can be obtained.

[0082] Softener Examples of softeners include petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and Vaseline; coal tar-based softeners such as coal tar; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; waxes such as beeswax and carnauba wax; naphthenic acid, pine oil, rosin or derivatives thereof; synthetic polymeric substances such as terpene resins, petroleum resins, and coumarone-indene resins; ester-based softeners such as dioctyl phthalate and dioctyl adipate; microcrystalline wax; liquid polybutadiene; modified liquid polybutadiene; hydrocarbon-based synthetic lubricating oils; tall oil; and sub(factice). Of these, petroleum-based softeners are preferred, and process oil is particularly preferred.

[0083] When a softener is used, the amount of the softener in the ethylene copolymer composition is preferably 2 to 100 parts by mass, more preferably 3 to 50 parts by mass, and further preferably 5 to 20 parts by mass, per 100 parts by mass of the copolymer (A).

[0084] ·Anti-aging agent The life of a seal packing formed from an ethylene copolymer composition can be extended by blending an antioxidant (stabilizer) with the composition. The antioxidant is a conventionally known antioxidant, such as an amine-based antioxidant, a phenol-based antioxidant, or a sulfur-based antioxidant.

[0085] Specific examples of the antioxidant include aromatic secondary amine antioxidants such as phenylbutylamine and N,N-di-2-naphthyl-p-phenylenediamine; phenolic antioxidants such as dibutylhydroxytoluene and tetrakis[methylene(3,5-di-t-butyl-4-hydroxy)hydrocinnamate]methane (trade name "Irganox 1010", manufactured by BASF); bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5- Examples of anti-aging agents include thioether-based anti-aging agents such as nickel dibutyldithiocarbamate, dithiocarbamate-based anti-aging agents such as nickel dibutyldithiocarbamate, and sulfur-based anti-aging agents such as 2-mercaptobenzoylimidazole (trade name "Sandant MB", manufactured by Sanshin Chemical Industry Co., Ltd.), 2-mercaptobenzimidazole, zinc salt of 2-mercaptobenzimidazole, dilauryl thiodipropionate, and distearyl thiodipropionate.

[0086] When an antioxidant is used, the blending amount of the antioxidant in the ethylene copolymer composition is preferably 0.3 to 10 parts by mass, more preferably 3.0 to 8.0 parts by mass, and further preferably 5.0 to 7.0 parts by mass, based on 100 parts by mass of the copolymer (A). When the blending amount of the antioxidant is within the above range, there is no bloom on the surface of the obtained molded article, and furthermore, the occurrence of vulcanization inhibition can be suppressed.

[0087] Processing aids As the processing aid (hereinafter also referred to as "processing aid (C)"), for example, a wide variety of processing aids that are generally compounded with rubber can be used. Specific examples of the processing aid (C) include fatty acids such as ricinoleic acid, stearic acid, palmitic acid, and lauric acid, fatty acid salts such as barium stearate, zinc stearate, and calcium stearate, and esters. Of these, stearic acid is preferred.

[0088] When the processing aid (C) is used, the blending amount of the processing aid in the ethylene copolymer composition is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 5.0 parts by mass, and further preferably 0.5 to 3.0 parts by mass, based on 100 parts by mass of the copolymer (A). When the blending amount of the processing aid is within the above range, it is preferable because the processability such as kneading processability, extrusion processability, and injection moldability is excellent.

[0089] ·Activators Examples of the activator include amines such as di-n-butylamine, dicyclohexylamine, and monoethanolamine; activators such as diethylene glycol, polyethylene glycol, lecithin, triaryl methylate, and zinc compounds of aliphatic or aromatic carboxylic acids; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcite, and special quaternary ammonium compounds.

[0090] When an activator is used, the amount of the activator in the ethylene copolymer composition is usually 0.2 to 10 parts by mass, preferably 0.3 to 5 parts by mass, based on 100 parts by mass of the copolymer (A).

[0091] <Method of producing ethylene copolymer composition> The ethylene-based copolymer composition forming the layer [I] can be prepared by kneading the copolymer (A) and other components to be blended as necessary at a desired temperature using a kneading machine such as an internal mixer (internal mixer) such as a Banbury mixer, a kneader, or an Intermix, or a roll.

[0092] Specifically, the ethylene copolymer composition can be prepared by kneading the ingredients at a predetermined temperature and time, for example, at 80 to 200°C for 3 to 30 minutes, using a conventionally known kneader such as a mixer or kneader, adding other components to be used as necessary to the kneaded mixture, and kneading the mixture using a roll at a predetermined temperature and time, for example, at a roll temperature of 30 to 80°C for 1 to 30 minutes.

[0093] 《Layer [II]》 The layer [II] containing a fiber material constituting the present laminate contains a fiber material in at least a part of the layer. The fiber material may be used alone or in combination of two or more kinds.

[0094] <Textile materials> Examples of fiber materials include various well-known fiber materials, for example, natural fibers such as cotton and wood cellulose fibers; organic fiber materials made of synthetic resins such as polyamide, polyester, polyvinyl alcohol, rayon, polyparaphenylene benzobisoxazole, polyethylene, polypropylene, polyarylate, polyimide, polyphenylene sulfide, polyether ether ketone, polylactic acid, polycaprolactone, polybutylene succinate, and fluorine-based polymers; and inorganic fiber materials such as glass fibers, PAN-based carbon fibers, pitch-based carbon fibers, alumina fibers, silicon carbide fibers, aluminum borate fibers, and potassium titanate whiskers.

[0095] Examples of the polyamide include aliphatic polyamides such as nylon 6, nylon 6,6, and nylon 6,10; semi-aromatic polyamides such as polymetaxylylene adipamide (MXD6), polyhexamethylene terephthalamide (6T), and copolymer polyamides containing these units; and fully aromatic polyamides such as polybenzamide, poly-p-phenylene terephthalamide, and poly-m-phenylene isophthalamide.

[0096] The fiber material may be a long fiber (filament) or a short fiber (staple). The fiber material may be a cord yarn, a spun yarn, or a canvas such as a woven fabric, a knitted fabric, or a nonwoven fabric.

[0097] The fiber material may be surface-treated by a known method such as RFL treatment in order to improve adhesion between the fiber materials themselves or between the fiber materials and the layer [I] made of the ethylene-based copolymer composition.

[0098] <Resorcinol-Formalin-Latex (RFL) Treatment> RFL treatment is a process in which textile materials are treated with a treatment liquid (RFL liquid) that contains resorcinol, formalin, and latex. The RFL liquid is a mixture of the initial condensation product of resorcinol and formalin and rubber latex. Examples of rubber latex that can be used include styrene-butadiene-vinylpyridine terpolymer (VP), styrene-butadiene copolymer (SBR), chloroprene (CR), acrylonitrile-butadiene copolymer (NBR), hydrogenated NBR (H-NBR), chlorosulfonated ethylene (CSM), and natural rubber. These can be used alone or in combination of two or more types.

[0099] <<Method for manufacturing the present laminate>> The laminate can be produced by any known method, as long as the layer structure is such that the layer [I] and the layer [II] are in contact with each other. For example, the laminate can be produced by laminating the layer [I] of an uncrosslinked ethylene copolymer composition produced (molded) by a known method with the layer [II] of a fiber material, and then crosslinking the layer [I], laminating the layer [I] of a crosslinked ethylene copolymer composition with the layer [II] of a fiber material, or extrusion coating the layer [I] of an uncrosslinked ethylene copolymer composition on the layer [II] of a fiber material, and then crosslinking the layer [I].

[0100] The layer [I] made of the ethylene-based copolymer composition can be produced by various known methods. For example, the uncrosslinked ethylene-based copolymer composition obtained by kneading according to the method for producing the ethylene-based copolymer composition can be molded into an intended shape by various molding methods such as an extruder, a calendar roll, a press, an injection molding machine, or a transfer molding machine. As described above, the material may be crosslinked after molding using the above method and then laminated (bonded) with a layer [II] containing a fiber material, or the material may be laminated (bonded) with a layer [II] containing a fiber material after molding and then crosslinked.

[0101] Examples of a method for crosslinking the layer [I] made of the ethylene-based copolymer composition include a method of heating using a crosslinking agent, and a method of irradiating with light, gamma rays, electron beams, or the like. Specifically, the layer [I] can be produced by introducing the layer [I] into a vulcanization tank simultaneously with or after molding, or after lamination with the layer [II], and heating at 120 to 270°C for 1 to 30 minutes, or by crosslinking by exposure to light, gamma rays, electron beams, etc.

[0102] Crosslinking may be performed using a mold or without a mold. When a mold is not used, the molding and crosslinking steps are usually performed continuously. Heating methods in the vulcanization tank can include hot air, glass bead fluidized bed, UHF (ultra-high frequency electromagnetic waves), steam, etc.

[0103] When a crosslinking method is used without using a crosslinking agent, for example, irradiation with an electron beam may be performed by irradiating layer [I] formed into a predetermined shape or laminated with layer [II] with an electron beam having an energy of usually 0.1 to 10 MeV, preferably 0.3 to 2 MeV, so that the absorbed dose is usually 0.5 to 35 Mrad, preferably 0.5 to 10 Mrad.

[0104] <<Uses of the laminate>> The laminate has a layer made of an ethylene copolymer composition having a high crosslinking rate, and the crosslinked molded article obtained has excellent heat aging resistance, so that it is excellent in productivity and is expected to have an extended product life. The laminate is suitably used for industrial hoses such as automobile hoses, water supply hoses, and gas hoses; industrial belts such as transmission belts and conveyor belts; escalator handrails, etc.

[0105] Examples of the hose for automobiles include brake hoses, radiator hoses, heater hoses, and air cleaner hoses. Examples of the power transmission belt include a V-belt, a flat belt, and a toothed belt. Examples of the conveyor belt include a light conveyor belt, a cylindrical belt, a rough top belt, a conveyor belt with a flange, a conveyor belt with a U-shaped guide, and a conveyor belt with a V-shaped guide. EXAMPLES

[0106] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "parts" refers to "parts by mass".

[0107] The physical properties of each copolymer used in the examples and comparative examples were measured as follows. (1) Weight fraction (mass%) and molar ratio The weight fraction (mass%) of each structural unit of the copolymer and the molar ratio of each structural unit are 13 The measured values ​​were obtained by C-NMR. The measured values ​​were obtained by using an ECX400P nuclear magnetic resonance apparatus (manufactured by JEOL Ltd.) at a measurement temperature of 120°C, a measurement solvent of orthodichlorobenzene / deuterated benzene = 4 / 1, and an accumulation number of 8000 times. 13 The C-NMR spectrum was obtained.

[0108] (2) Number of branch points BrNo The number of branching points BrNo of the copolymer was calculated by structural analysis from the absolute molecular weight distribution and intrinsic viscosity obtained using a 3D-high temperature GPC device (PL-GPC220 model, Polymer Laboratories). The main measurement conditions are as follows. The dn / dc value required to determine the absolute molecular weight was calculated for each sample from the dn / dc value of standard polystyrene (molecular weight 190,000) of 0.053 and the response intensity of the differential refractometer per unit injected mass. Detector: Differential refractometer / GPC device built-in 2-angle light scattering photometer PD2040 type (manufactured by Precison Detectors) Bridge type viscometer PL-BV400 (Polymer Laboratories) Column: TSKgel GMH HR -H(S)HT x 2 + TSKgel GMHHR -M(S) x 1 (each with inner diameter of 7.8mmφ x length of 300mm, manufactured by Tosoh Corporation) Column temperature: 140℃ Mobile phase: 1,2,4-trichlorobenzene (containing 0.025% BHT) ·Injection volume: 0.5mL Sample concentration: ca 1.0mg / mL Sample filtration: Filtration through a sintered filter with a pore size of 1.0 μm

[0109] The relationship between the intrinsic viscosity obtained by the viscometer and the absolute molecular weight obtained by the light scattering photometer was used to determine the elution composition. Long chain branching parameter g' per minute i was calculated from the following formula (v-1).

[0110]

number

[0111]

number

[0112] Furthermore, the number of branch points per molecular chain, BrNo, was calculated using g'w. BrNo was calculated using the following Zimm-Stockmayer formula (v-5). Here, g is the long chain branching parameter calculated from the radius of gyration Rg, and the following simple correlation is made between g' calculated from the intrinsic viscosity: g=g' (1 / ε) (ε(structure factor)=0.5~1.5) Various values ​​have been proposed for ε in the formula depending on the shape of the molecule. Here, the calculation was performed assuming ε = 1 (i.e. g' = g).

[0113]

number

[0114] (3) Intrinsic viscosity [η] The intrinsic viscosity [η] (dl / g) of the copolymer was measured using a fully automatic intrinsic viscometer manufactured by Rigo Co., Ltd. at a temperature of 135° C. and in decalin as a measurement solvent.

[0115] (4) Weight average molecular weight (Mw) The weight average molecular weight (Mw) of the copolymer was determined using a 3D-high temperature GPC apparatus (PL-GPC220, manufactured by Polymer Laboratories) under the same measurement conditions as in (2) above.

[0116] (5) Mooney viscosity The Mooney viscosity ML(1+4)100° C. of the copolymer was measured using a Mooney viscometer (SMV-301 model, manufactured by Shimadzu Corporation) in accordance with JIS K 6300 (1994).

[0117] (6) Complex viscosity η * and P value The rheometer used was the Ares viscoelasticity measuring device (manufactured by Rheometric Scientific), and the complex viscosity η at a frequency of ω = 0.01 rad / s was measured under the conditions of 190°C and 1.0% strain. * (ω=0.01) , complex viscosity η at frequency ω=0.1rad / s * (ω=0.1) , complex viscosity η at frequency ω=10rad / s * (ω=10) and the complex viscosity η at frequency ω = 100 rad / s * (ω=100) (All units are Pa·sec.)

[0118] In addition, the obtained results show that η * (ω=0.1) and η* (ω=100) The P value (η * (ω=0.1) / η * (ω=100) ) was calculated.

[0119] (7) Glass transition temperature (Tg) The glass transition temperature (Tg) of the copolymer was determined by DSC measurement under the following conditions. Using a differential scanning calorimeter (RDC220, manufactured by SII), approximately 10 mg of a sample was heated from 30°C to 200°C at a heating rate of 50°C / min in a nitrogen atmosphere and held at that temperature for 10 minutes. It was then cooled to -100°C at a heating rate of 10°C / min, held at that temperature for 5 minutes, and then heated to 200°C at a heating rate of 10°C / min.

[0120] The glass transition temperature (Tg) is detected as the DSC curve bending due to the change in specific heat during the second heating, and the baseline shifts in parallel. The glass transition temperature (Tg) is determined as the temperature at the intersection of the tangent to the baseline lower than this bending and the tangent to the point where the slope of the bending part is maximum.

[0121] [Ethylene-α-olefin-non-conjugated polyene copolymer (A)] In the following examples, copolymer (A-1) obtained in the following Production Example 1 was used as copolymer (A).

[0122] <Production Example 1> A polymerization reaction of ethylene, 1-butene, and 5-vinyl-2-norbornene (VNB) was continuously carried out at 95°C using a 300 L volume polymerization vessel equipped with an agitator. Hexane (feed rate: 30.5 L / h) was used as the polymerization solvent and was continuously fed to the polymerization reactor so that the ethylene feed rate was 5.3 kg / h, the 1-butene feed rate was 21.5 kg / h, the VNB feed rate was 566 g / h, and the hydrogen feed rate was 10 NL / h.

[0123] While maintaining the polymerization pressure at 1.6 MPaG and the polymerization temperature at 95°C, di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride was used as the main catalyst and continuously fed to the polymerization reactor at a feed rate of 0.00903 mmol / h. In addition, (C6H5)3CB(C6F5)4 was continuously fed to the polymerization reactor at a feed rate of 0.045 mmol / h as a cocatalyst, and triisobutylaluminum (TIBA) was continuously fed to the polymerization reactor at a feed rate of 30 mmol / h as an organoaluminum compound.

[0124] In this way, a solution containing 20% ​​by mass of ethylene-1-butene-VNB copolymer formed from ethylene, 1-butene and VNB was obtained. A small amount of methanol was added to the polymerization reaction liquid withdrawn from the bottom of the polymerization vessel to terminate the polymerization reaction, and the ethylene-1-butene-VNB copolymer was separated from the solvent by steam stripping and then dried under reduced pressure at 80°C for a whole day and night.

[0125] By the above operations, ethylene-1-butene-VNB copolymer (A-1) was obtained at a rate of 8.5 kg per hour. The physical properties of the obtained copolymer (A-1) were measured by the methods described above. The results are shown in Table 1.

[0126] [Ethylene-1-butene-ENB copolymer (E-1)] In the following Comparative Example, the copolymer (E-1) obtained in the following Production Example 2 was used. <Production Example 2> According to the description of [Synthesis Example C1] of WO 2015 / 122415, an ethylene-1-butene-5-ethylidene-2-norbornene (ENB) copolymer (E-1) having the following physical properties was obtained. The physical properties of the obtained copolymer (E-1) were measured by the method described above. The results are shown in Table 1.

[0127] [Table 1]

[0128] [Example 1] <<Preparation of Ethylene-Based Copolymer Composition>> The copolymer (A-1) was masticated for 30 seconds, and then 100 parts by mass of the masticated copolymer (A-1), 5 parts by mass of ZnO#1 / zinc oxide type 2 (manufactured by Hakusui Tech Co., Ltd.) as a crosslinking aid, 1 part by mass of stearic acid as a processing aid (C), 4 parts by mass of Sandant MB (trade name; 2-mercaptobenzimidazole, manufactured by Sanshin Chemical Industry Co., Ltd.) as an antiaging agent, and Irganox 1010 (trade name; tetrakis[methylene(3,5-di- Two parts by weight of tert-butyl-4-hydroxy)hydrocinnamate [methane, manufactured by BASF], 50 parts by weight of Asahi #70 (trade name, manufactured by Asahi Carbon Co., Ltd.) as a filler, and 10 parts by weight of Diana Process Oil PW-380 (trade name, manufactured by Idemitsu Kosan Co., Ltd.) as a softener were mixed together in a Banbury mixer (manufactured by Kobe Steel, Ltd., volume 1.7 L) at a rotor rotation speed of 50 rpm and a floating weight pressure of 3 kg / cm. 2 The mixture was mixed for 2 minutes at 150° C. The ram was then raised and cleaned, and the mixture was mixed for another minute and discharged at about 150° C. to obtain a compound. The mixture was mixed at a filling rate of 70%.

[0129] Next, after confirming that the temperature of the compound had reached 40°C, it was wound around an 8-inch roll (front roll surface temperature 50°C, rear roll surface temperature 50°C, front roll rotation speed 16 rpm, rear roll rotation speed 18 rpm), and 6.8 parts by mass of dicumyl peroxide (DCP) (40% masterbatch, product name: DPC-40C, manufactured by Kayaku Akzo Co., Ltd.) was added as crosslinking agent (B) to 172 parts by mass of Compound 1, and kneaded for 10 minutes, after which it was separated into a sheet to prepare an unvulcanized sheet having a thickness of 2 mm.

[0130] <Evaluation of physical properties of unvulcanized sheets> [Crosslinking (vulcanization) characteristic evaluation] The crosslinking rate tC90 of the uncrosslinked sheet was measured as follows using a vulcanization measuring device: MDR2000 (manufactured by ALPHA TECHNOLOGIES). The torque change obtained under the conditions of a constant temperature and a constant shear rate was measured. The difference S'Max-Min [dNm] between the maximum torque S'Max [dNm] and the minimum torque S'Min [dNm], the time TS1 [min] when the torque of the measured sample increased by 1 dNm after reaching the minimum torque S'Min, and the time tC90 [min] when the torque of the measured sample reached 90%, assuming the minimum torque S'Min to be 0% and the maximum torque S'Max to be 100%, were calculated. The measurement conditions were a temperature of 170°C and a time of 30 minutes. The smaller this tC90, the faster the vulcanization speed (crosslinking speed).

[0131] Evaluation of physical properties of vulcanized (crosslinked) products The obtained unvulcanized sheet was pressed at 170° C. for 15 minutes using a 100-ton press molding machine to produce a vulcanized sheet (vulcanized product (crosslinked product)) having a thickness of 2 mm. The vulcanized sheets thus obtained were subjected to a hardness test, a tensile test, and a heat aging resistance test by the following methods.

[0132] [Hardness test: Hardness (Durometer-A (shore-A))] The hardness of the sheet was measured in accordance with the description of "Hardness test" in Section 7 of JIS K 7312 (1996) "Physical test methods for thermosetting polyurethane elastomer moldings" and the description of Test Type A in Section 6 of JIS K 6253 (2006) "Vulcanized rubber and thermoplastic rubber - Determination of hardness".

[0133] [Tensile test: tensile stress at break, tensile elongation at break] The modulus, tensile stress at break, and tensile elongation at break of the sheet were measured by the following methods. The sheet was punched out to prepare a No. 3 dumbbell test piece described in JIS K 6251 (1993). Using this test piece, a tensile test was performed according to the method specified in JIS K 6251, section 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min, and the tensile stress at break TB [MPa] and the tensile elongation at break EB [%] were measured.

[0134] [Heat aging test] The sheet was subjected to a heat aging test at 180° C. for 70 hours according to JIS K 6257. The hardness, tensile stress at break, and tensile elongation at break of the sheet after the heat aging test were measured in the same manner as in the above items [Hardness (Durometer-A)] and [Tensile stress at break, tensile elongation at break].

[0135] AH (shore-A) was calculated from the difference in hardness before and after the heat aging test, and the rate of change after the test from the values ​​before the heat aging test to the values ​​before the test was calculated as Ac(TB) and Ac(EB), respectively, from the tensile stress at break (TB) and tensile elongation at break (EB) before and after the heat aging test.

[0136] [Comparative Example 1] The same procedure as in Example 1 was carried out, except that the copolymer (E-1) was used instead of the copolymer (A-1) used in Example 1. The results are shown in Table 2.

[0137] [Table 2]

[0138] As shown in Table 2, the composition containing copolymer (A-1) (Example 1) had a faster crosslinking rate and was more productive than the composition containing copolymer (E-1) (Comparative Example 1), and the crosslinked molded article obtained had better heat aging resistance.

Claims

1. A laminate comprising a layer [I] made of an ethylene-based copolymer composition containing an ethylene-α-olefin-non-conjugated polyene copolymer (A) and a layer [II] containing a fiber material, the layer [I] and the layer [II] being in contact with each other, The copolymer (A) has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, A laminate, wherein the structural unit derived from the non-conjugated polyene [A3] contains a structural unit derived from 5-vinyl-2-norbornene: 【Chemistry 1】 Requirement (1): the molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2] and a non-conjugated polyene [A3], and [EX] represents the ethylene [A1]-α-olefin having 4 to 20 carbon atoms [A2] dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC, satisfies the following formula (ii): BrNo≧0.5...Formula (ii)

2. The laminate according to claim 1, wherein the copolymer (A) satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (wt%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Requirement (6): Complex viscosity η at a frequency ω = 0.1 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * (ω=0.1) (Pa sec) and the complex viscosity η at a frequency ω = 100 rad / s * (ω=100) (Pa sec) P [η * (ω=0.1) / * (ω=100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of the [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ weight fraction of [A3] × 6 ... formula (iv) Requirement (7): Complex viscosity η at a frequency ω = 0.01 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * (ω=0.01) (Pa sec) and the complex viscosity η at a frequency ω = 10 rad / s * (ω=10) (Pa·sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v); Log{η * (ω=0.01) } / Log{η * (ω=10) }≦0.0753×{apparent iodine value derived from the non-conjugated polyene [A3]}+1.42 ... formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −65° C. or lower.

3. 2. The laminate according to claim 1, wherein the Mooney viscosity ML(1+4) 100° C. of the copolymer (A) is 5 to 150.

4. The laminate according to claim 1 , wherein the ethylene-based copolymer composition contains an organic peroxide as the crosslinking agent (B).

5. The laminate according to claim 1, wherein the ethylene-based copolymer composition contains 0.1 to 20 parts by mass of a processing aid (C) based on 100 parts by mass of the copolymer (A).

6. The laminate according to claim 1 , wherein the ethylene-based copolymer composition is crosslinked.

7. 2. The laminate according to claim 1, wherein the fibrous material of the layer [II] comprises resorcinol-formaldehyde latex-treated fibers.

8. The laminate according to claim 1, wherein the textile material of the layer [II] is canvas.

9. An industrial belt comprising the laminate according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Ethylenic copolymer composition and applications thereof

    JP2021161258A